The coal-forming environment during mass extinction in the latest permian: Evidence from geochemistry of rare Earth elements - Wang, Juan; Shao, Longyi; Yan, Zhiming; Wang, Xuetian (Frontiers in Earth Science, 2023)
An analysis of Rare Earth Elements (REEs) was conducted on the C1 coal from the Yantang Mine of Xuanwei, eastern Yunnan Province, which was deposited during the latest Permian. A total of 24 samples from coals, partings, roofs and floors from the C1 coal were taken from the fresh face in the underground mine. The results of the REEs analysis indicated that the total REE content (∑REE) in the C1 coal varies from 23.99 µg/g to 267.94 µg/g, averaged 122.69µg/g. The C1 coal is enriched in light REE (LREE) relative to heavy REE (HREE), signifying the fractionation between LREE and HREE. Most samples of the coal seam C1 are depleted in Eu in various degrees and slightly depleted in Ce, especially two partings in sub-seams B1 and B3 which show the significant negative Eu anomalies. The geochemical characteristics of REE reveal that the C1 coal was deposited in a weak oxidation environment; the sedimentary environment was turbulent during the middle-later stage of coal-forming process; the C1 coal was affected by the basalt clastic materials from the Khangdian Oldland and acidic synsedimentary volcanic ash in the coal-forming period. The geochemical characteristics of Tonsteins in C1 coal are similar to those of marine Permian-Triassic boundary (PTB) volcanic ash layers in South China, which are both derived from the felsic volcanism caused by the closure of the Paleo-Tethys at the southwestern margin of the South China. Furthermore, the C1 coal was also affected by the eruption of Siberian large igneous province (SLIP) in the early stage.